2013
DOI: 10.1007/s12594-013-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Isotopic Compositions of Groundwater and Stream Water in a Heavy Agricultural Basin of Korea

Abstract: The chemical and isotopic compositions of groundwater and stream water in the Haean basin, Korea, which have been intensively used for agricultural irrigation, were examined. The field parameters and chemical compositions were typical of relatively uncontaminated waters, except for the agricultural impact. The low EC levels indicated that the waters had not experienced any significant geochemical processes such as water-rock interaction and evaporation. The very similar chemical compositions and ionic ratios w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It is bordered by high elevation mountains with altitudes of 1147-1242 m. The lowermost area of the basin has an elevation of about 400 m. Forests cover the uppermost areas, while the lower areas are mostly used for agriculture. This unusually deep depression was formed by differential weathering between meta-sedimentary rocks at the outer rim and granites in the interior [29]. Alluvial deposits are found close to streams in the flat areas.…”
Section: Study Areamentioning
confidence: 97%
See 3 more Smart Citations
“…It is bordered by high elevation mountains with altitudes of 1147-1242 m. The lowermost area of the basin has an elevation of about 400 m. Forests cover the uppermost areas, while the lower areas are mostly used for agriculture. This unusually deep depression was formed by differential weathering between meta-sedimentary rocks at the outer rim and granites in the interior [29]. Alluvial deposits are found close to streams in the flat areas.…”
Section: Study Areamentioning
confidence: 97%
“…Most groundwater recharged by rainfall quickly reaches the stream. Therefore, the chemical compositions and isotopic compositions of groundwater are not significantly distinguished from those of stream water [29]. Geological investigations revealed that there are typically six hydrogeological layers in the lowlands: surface reclamation soil, sand and gravel, scree, weathered rock, soft rock with fractures, and fresh hard rock [28].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations